It is time to rewrite state youth sports concussion laws. Issue 1 (6th January 2021) - Howland, Jonathan; Hackman, Holly; Torres, Alcy; Campbell, Julia; Olshaker, Jonathan
Abstract : Between 2009 and 2014, all 50 states and the District of Columbia passed legislation to improve the recognition and management of youth concussed in sports. These laws can include requirements for concussion training for school athletic personnel, concussion education for children and their parents, return-to-play (RTP) procedures, and medical clearance to for RTP. Concussion can impact academic learning and performance in children and adolescents. Postconcussion academic accommodations during recovery can be an important component of secondary prevention for mitigating the sequalae of head injury. Few state youth concussion laws, however, include provision of postconcussion return-to-learn (RTL) accommodations and most of those that do address RTL apply to student athletes only. Concussions may occur in youth who are not participating in organised sports (eg, falls, traffic crashes) and thus may not be subjected to RTL accommodations, even if the state mandates such procedures for athletes. Low income and students of colour may be more likely to have non-sports concussions than their more affluent and white peers, thus potentially creating demographic disparities in the benefits of RTL procedures. State youth sports concussion laws should be revised so that they include RTL provisions that apply to all students, athletes and non-athletes alike.